2012
DOI: 10.1111/j.1447-0756.2012.02045.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin versus sustained‐release dinoprostone vaginal pessary for labor induction of unfavorable cervix with Bishop score ≥4 and ≤6: A randomized controlled trial

Abstract: Intravenous oxytocin is effective to stimulate labor at term for patients with Bishop scores ≥ 4 and ≤ 6, with a shorter time interval from induction to vaginal delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 41 publications
4
26
1
Order By: Relevance
“…Of the 103 trials identified, just 63 were RCTs. 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 The majority of RCTs were single-center trials conducted in academic hospitals, which can limit the generalizability of the results to other community-based populations. Among the 12 multicenter trials, the number of centers ranged from 2 to 49 and tended to include both university-affiliated and community hospitals.…”
Section: Limitations Of Trials On Labor Inductionmentioning
confidence: 99%
“…Of the 103 trials identified, just 63 were RCTs. 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 The majority of RCTs were single-center trials conducted in academic hospitals, which can limit the generalizability of the results to other community-based populations. Among the 12 multicenter trials, the number of centers ranged from 2 to 49 and tended to include both university-affiliated and community hospitals.…”
Section: Limitations Of Trials On Labor Inductionmentioning
confidence: 99%
“…[15] In the literature, the studies comparing intravenous oxytocin and dinoprostone use during the induction of labor showed that dinoprostone causes less delivery failure than oxytocin and it is more effective and reliable method, [16][17][18] the study conducted by Koç et al comparing oxytocin and dinoprostone reported that labor occurred in a short time by oxytocin and caused less cesarean delivery even there is no statistical significance. [19] In our study, we found that active labor phase was significantly shorter although latent duration was longer in dinoprostone group compared to oxytocin group (p=0.000). Mazouni C et al indicated in their study that there was no maternal and fetal morbidity in patients applied dinoprostone while the caesarean rate was 3.5 times more.…”
Section: Discussionmentioning
confidence: 45%
“…32 However, one of the trials is limited by the fact that oxytocin was not administered subsequent to DVI which is not typical practice. Boulvain et al 30 analyzed 11 trials of intracervical versus vaginal prostaglandin gel.…”
Section: Pge2mentioning
confidence: 99%